The Congress of Vienna, 1814-1815: diplomacy, political culture and sociability - Kwan, Jonathan (Cambridge University press, 2017)
On 29 November 1814, the Austrian Emperor Francis, the Russian Tsar Alexander, and the Prussian King Frederick Wilhelm, along with 6,000 others, attended a concert in Vienna's Redouten Hall; Beethoven personally conducted three of his works: the Seventh symphony, the bombastic ‘Wellington's victory’, and a newly written cantata entitled ‘The glorious moment’. In this cantata, the figure of ‘Vienna’ sings the following words: Oh heaven, what delight! What spectacle greets my gaze! All that the earth holds in high honour Has assembled within my walls! My heart throbs! My tongue stammers! I am Europe – no longer one city.